Two Sides of Peer Support: A Qualitative Study on Peer Influence and Alcohol Consumption among Students at Universitas Negeri Makassar - Awaru, A. Octamaya Tenri; Syukur, Muhammad; Wahidin, Wahidin; Ramadhany, A. Noer Chalifah (Humaniora, 2025)
This study aims to explore how social support and social relationships are perceived and experienced by university students who consume alcoholic beverages on campus, and how these factors relate to expressions of aggressiveness. The research is motivated by the growing concern over aggressive behaviors among students involved in alcohol consumption, as well as the limited number of studies that address this issue from a social and cultural perspective. Previous research has predominantly employed quantitative approaches or focused on individual psychological factors. To address this gap, the present study adopts a descriptive qualitative approach with an interpretivist orientation, aiming to uncover the meanings and lived experiences of students. Eight active students from the Gunungsari campus of Universitas Negeri Makassar were selected as participants using purposive sampling. Data were collected through in-depth interviews and analyzed using data condensation, data display, and conclusion drawing and verification. The findings reveal that forms of social support emotional, informational, and instrumental as well as social relationships characterized by cooperation, accommodation, and assimilation, shape how students interpret and respond to situations involving alcohol use and aggression. These results suggest that aggressive behavior is not solely an individual response but is deeply embedded in the surrounding social context. This study contributes to the literature on student behavior and mental health from a socio-cultural perspective, particularly within the context of higher education in Indonesia.